Destination Branding Through Semiotics Analysis of Video Wonderful Indonesia 2018 ‘The More You Feel, The More You Know’ - Jessica Renanda (Kata Kita: Journal of Language, Literature, and Teaching, 2020)
In this study, by using the destination brand benefit pyramid and semiotics theories, the writer aimed to analyze the destination branding of Indonesia’s Tourism through semiotics analysis in visual and verbal expressions of video Wonderful Indonesia 2018 ‘The More You Feel The More You Know’. In this video, Indonesia’s tourism 2018 is highlighting three main destinations: East Nusa Tenggara, Bali and Yogyakarta. The writer also analyzed the rational benefits, emotional benefits, destination brand values (personality) and the brand essence of Indonesia’s tourism: Wonderful Indonesia. The writer uses qualitative content analysis as approach of study. As the conclusion, the writer found  that visiting Indonesia as the biggest archipelago of the world is more than just a leisure activities, but is about a journey to discover and to feel the real essence of Indonesia - a wonderful country, not just because of its natural wonders that are exist nowhere else in the world, but also because of the cultural traditions that are full of moral values which are inherited and ingrained from generation to generation as the identity as well as the characters of Indonesian people. Keywords: Destination branding, destination brand benefits, verbal and visual expressions.